Peran Media Sosial Instagram @pandawaragroup sebagai Media Kampanye dalam Menjaga Lingkungan - Risa Sabila Risa Sabila; Yusmar Yusuf (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
By focusing on the @pandawaragroup account in particular, this study intends to dissect the function of Instagram as a platform for environmental advocacy campaigns. Global environmental difficulties, including pollution, deforestation, and climate change, need community engagement and are driving this study. A collective of young individuals hailing from Bandung, Indonesia, run the @pandawaragroup account on Instagram. They want to raise awareness about environmental issues by sharing engaging and educational visual material. Eighty posts from the @pandawaragroup account during October and November 2024 were analyzed as part of the descriptive qualitative study technique. Relevance to environmental concerns, communication tactics, and audience reactions were the criteria utilized to evaluate these posts. Symbolic interactionism theory is also used in this study to understand how social media content's symbols create collective meaning that inspires actual action. Findings from this study highlight the significance of the @pandawaragroup account in bringing environmental concerns to the attention of the general population. This account has had great success in generating audience engagement—comments, likes, and involvement in environmental campaigns—through the use of visual-based communication methods including films, infographics, and cooperation with other groups. According to these findings, Instagram in particular might be a powerful social media tool for campaigns advocating for environmental protection.